Development of anti‐migraine therapeutics using the capsaicin‐induced dermal blood flow model. (6th October 2015) - Buntinx, Linde; Vermeersch, Steve; de Hoon, Jan
Abstract : The efficacy of calcitonin gene‐related peptide (receptor) (CGRP‐(R)) blocking therapeutics in the treatment of acute migraine headache provided proof‐of‐concept for the involvement of CGRP in the pathophysiology of this disorder. One of the major hurdles for the development of any class of drugs, including CGRP blocking therapeutics, is the early clinical development process during which toxic and inefficacious compounds need to be eliminated as early as possible in order to focus on the most promising molecules. At this stage, human models providing proof of target engagement, combined with safety and tolerability studies, are extremely valuable in focusing on those therapeutics that have the highest engagement from the lowest exposure. They guide the go/no‐go decision making, establish confidence in the candidate molecule by de‐risking toxicity and safety issues and thereby speed up the early clinical development. In this review the focus is on the so called 'capsaicin model' as a typical example of a target engagement biomarker used as a human model for the development of CGRP blocking therapeutics. By applying capsaicin onto the skin, TRPV1 channels are activated and a CGRP‐mediated increase in dermal blood flow can be quantified with laser Doppler perfusion imaging. Effective CGRP blocking therapeutics in turn, display blockade of this response. The translation of this biomarker model from animals to humans is discussed as well as the limitations of the assay in predicting the efficacy of anti‐migraine drugs.